Could an understanding of the strawberry softening process benefit from Aquaporins - Alleva, Karina Edith (2011)
Strawberry is the most economically important soft fruit characterized by its delicious flavour, intense colour and soft texture. The rapid loss of firmness during strawberry ripening is the main determining factor of its short shelf life, and great losses occur by bruising, oversoftening and subsequent fungal infections during postharvest transportation and storage. Cell wall disassembly and the reduction of cell to cell adhesion due to middle lamella dissolution have been recognized as the main causes of fruit softening. In the case of strawberry fruit, cell wall disassembly during ripening is characterized by a solubilization of pectins, a slight depolymerization of covalently bound pectins, a loss of galactose and arabinose, as well as a reduction in the hemicellulosic content. The genetic manipulation of genes encoding proteins involved in wall disassembly has been explored as a biotechnological approach to reduce fruit softening. Thus, the silencing of fruit specific pectate lyase or polygalacturonase genes, both acting on demethylated pectins, by antisense transformation increased significantly the firmness of ripe strawberry fruit without affecting other fruit quality parameters. By contrast, the down-regulation of the expression of genes involved in the processing of hemicellulosic polymers, such as endo-b-1,4-glucanase or expansin genes, did not modify fruit firmness. Other cell wall genes, e.g. b-xylosidase, b-galactosidase, α-arabinofuranosidase, have been cloned in strawberry fruit, and their expression analyzed along fruit development, but their function on fruit softening has not been assessed yet by transgenic approaches. Overall, these results indicate that pectin processing during ripening is a critical factor in the softening of strawberry fruit, and the manipulation of this process by down-regulating pectinase genes a successful approach to improve this trait. This review summarizes recent progress on strawberry fruit softening, focusing in the role of cell wall disassembly and genes involved in that process.